If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 6x = 7x + 3 Reorder the terms: 2 + 6x = 3 + 7x Solving 2 + 6x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + 6x + -7x = 3 + 7x + -7x Combine like terms: 6x + -7x = -1x 2 + -1x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + -1x = 3 + 0 2 + -1x = 3 Add '-2' to each side of the equation. 2 + -2 + -1x = 3 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 3 + -2 -1x = 3 + -2 Combine like terms: 3 + -2 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| (5/x)=(40/90) | | 5/x=40/90 | | 2/3y+13 | | (7x-5)(7x-5)=0 | | y-130=-13/2 | | 6v^2+5v+1=0 | | (4x^2-3x^3)-(7x^2-9x^3)=0 | | 6X+66=8X-26 | | 2X+132=8X+90 | | 8X+18=6X+40 | | (-4x^2y)(x^5y^2)=0 | | 2X+130=7X+55 | | 7/x=200/1100 | | -x^2+14x-24= | | 2x-7=9-6x | | 4x-5/x+1=0 | | 8y^2-18y+13=0 | | 9X+168=5X+144 | | (1/4x)-(5/6x)=4-(7/2x) | | 28+18t+2t^2= | | 7t-19=-24+6t | | 16.12=-0.5x^2+0.5x+28 | | 8p-15=-18+7p | | 7-81=p | | (2/(8x+7))=(5/(x+3)) | | 2n=2.5(n-4) | | -3a-5[2a-2[2a-(4a-2)-2(7-3a)]]= | | 6x-10(-2.4)=30 | | (0.75+z)-(z/0.5)=0.25 | | 6-10y=30 | | 5(3+3X)-3=87 | | 5x^2y+75xy-35y= |